Engineering research to improve cassava processing technology - Kolawole, O.P.; Agbetoye, L.A.S. (Walter de Gruyter GmbH, 2007)
Cassava is an important food crop, and equipment development for processing it in the developing world requires more research as industrial processing of cassava is still limited. Research efforts made by local engineers need scientific improvement to meet the Millennium Development Goals (MDGs), aimed at poverty reduction over a stipulated period of time with globally defined measurable indicators of progress. The World Summit on Sustainable Development (WSSD), the Report of the Commission for Africa (popularly referred to as the Tony Blair Report), and the New Partnership for African Development (NEPAD) are targeted at re-positioning Africa in the world economy. The need for rapid cassava processing equipment and new equipment development to significantly improve stages involved in its production process is highlighted in this paper.